Financial development and international trade towards economic growth / Amirah Diyanah Azman - Azman, Amirah Diyanah (Faculty of Business Management, 2017)
The global economy in the world is having an incredibly growing. It is also affecting economic growth in Malaysia. In relation to that, Malaysia economy in terms of real GDP per capita has also grown tremendously from time to time. In addition, the financial developments in the country also being develop and the international trade of the country also encourage exports and imports of the goods and services. These encourage development seem to indicate that there is a relationship between financial development, international trade and economic growth. Thus, the aim of the study is to investigate the relationship between financial developments, international trade toward economic growth in Malaysia starting from year 1960 until 2016. The data contain 57 of observations. The dependent variable in this study is gross domestic product per capita (constant local currency) while the independent variable are broad money and domestic credit to private sector as indicator for financial development and also exports of goods and services and imports of goods and services are taking as indicator for international trade. Based on previous research, the expected finding for financial development and international trade is positive relationship towards the economic growth. This study applied Ordinary Least Square (OLS) test as a method in regression.